Synthetic Birdsongs as a Tool to Induce, and Iisten to, Replay Activity in Sleeping Birds - Amador, Ana (2021)
Birdsong is a complex vocal behavior, which emerges out of the interaction between a nervous system and a highly nonlinear vocal device, the syrinx. In this work we discuss how low dimensional dynamical systems, interpretable in terms of the biomechanics involved, are capable of synthesizing realistic songs. We review the experimental and conceptual steps that lead to the formulation of low dimensional dynamical systems for the song system and describe the tests that quantify their success. In particular, we show how to evaluate computational models by comparing the responses of highly selective neurons to the bird’s own song and to synthetic copies generated mathematically. Beyond testing the hypothesis behind the model’s construction, these low dimensional models allow designing precise stimuli in order to explore the sensorimotor integration of acoustic signals.